حقوقِ مجردہ اور ان کےاحکام: ایک مطالعہ (Al-Qamar, 2020)
This article deals with the rules of al-Ḥuqūq al-Mujarrada in Islamic jurisprudence. It explores that Withdrawal from abstract rights without any compensation has unanimously been permitted by the scholars. Inheritance and wills are not issued for essential rights. In the rest of abstract rights, inheritance and will issued according to the most of Ḥanafī scholars. As far compensation for essential rights is concerned, it is not permissible. However, it is permissible to take compensation as a withdrawal. The sale of consensual rights is permissible according to the majority and contemporary jurists, while the sale of some rights is permissible according to the classical Ḥanafī scholars. Similarly, the sale and compensation of modern forms of abstract rights is not permissible according to some scholars, but it is permissible according to the majority of contemporary jurists.
Keywords: Al-Ḥuqūq al-Mujarrada; Fiqh; permissibility; impermissibility